Conceptual Framework for Public Policymaking based on System Dynamics and Big Data - Feldiansyah Bin Bakri Nasution; Dr. Nor Erne Nazira Bazin; Dr. Hasanuddin Hasanuddin (IAES Indonesia Section, 2017)
Public policy is the critical key of the welfare programs. It is also a powerful instrument to achieve a feasible national competitiveness. Unfortunately, many public policy making processes does not utilize an appropriate data and tool in holistic and systematical approach. This research will focus on creating a comprehensive conceptual framework for public policymaking based on data and system approach. In connection with information technology, there are at least two approaches that will be considered for obtaining a more comprehensive public policy. First is utilization of Big Data to extract information. It is believed that if more accurate data are collected and analyzed, then more comprehensive public policy is created. Utilization of data mining will be intensively used to obtain knowledge. The second approach is the system dynamics. The knowledge created in the first approach is useful in modeling the system. The model will be used to simulate the future possibilities of several scenarios. The scenario with the best outcome is selected as an input for public policymaking. At the end of this research, a conceptual framework for public policy making will be created by incorporating Big Data and system dynamics.